Navigating New Normals: Student Perceptions, Experiences, and Mental Health Service Utilization in Post-Pandemic Academia - Hadiza Galadima; Anne Dumadag; Cara Tonn (MDPI AG, 2024)
This study explores the profound impacts of the COVID-19 pandemic on higher education, focusing on shifts in learning experiences and students' intentions to utilize mental health services post-pandemic. Utilizing Andersen's Behavioral Model of Health Services Use, this study assesses perceptions from a stratified random sample of college students on post-pandemic learning experiences and mental health service utilization intentions. Findings reveal a positive reception to university initiatives and a preference for ongoing virtual classes. There is an evident increase in, and varying intentions for, using mental health services, shaped by demographics, employment, and prior service utilization. Younger and female students showed an increased propensity to seek such services. This research underscores the urgent need for universities to bolster support for mental health and create awareness, alongside accommodating diverse learning preferences in transitioning back to traditional learning post-pandemic.